A curve in the road - MacLean, Julianne (Lake Union Publishing, 2018)
Abbie MacIntyre is living the dream in the picturesque Nova Scotia town she calls home. She is a successful surgeon, is married to a handsome cardiologist, and has a model teenage son who is only months away from going off to college. But then one fateful night, everything changes. When a drunk driver hits her car, Abbie is rushed to the hospital. She survives, but the accident forces unimaginable secrets out into the open and plagues Abbie with nightmares so vivid that she starts to question her grip on reality. Her perfect life begins to crack, and those cracks threaten to shatter her world completely. The search for answers will test her strength in every way--as a wife, a career woman, and a mother--but it may also open the door for Abbie to move forward, beyond anger and heartbreak, to find out what she is truly made of. In learning to heal and trust again, she may just find new hope in the spaces left behind.